Takbiran Festival: Cultural Public Sphere and its Contribution in The Social Media Era - Rianto, Puji; Sulkhan, Khumaid Akhyat; Setiawati, Titin (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
The Takbir festival has become an annual ritual for Muslims in Yogyakarta. Festivals are held in many places and organized by local communities. This research was conducted to investigate the Takbir festival by seeing it as a cultural public sphere and how it contributes in the era of digital media. The research used a qualitative field research approach. Data was collected through interviews, observation, and documentation. The research results show that the Takbir festival has exceeded its traditional function as a broadcast medium of Islam. On the contrary, the takbir festival has presented itself as a cultural public sphere where various cultures are displayed through various elements such as mascots, traditional clothing, musical instruments, and other ornaments used by each participant. These cultural expressions are the participants' interpretations in translating the festival theme, namely Caring for The World and Civilization. Participants translated the interpretation into various cultural expressions. These expressions basically display a political articulation of certain events, which are linked to their interpretation of the festival theme. There are two political positions that can be identified from the way the festival participants interpret the theme, namely Caring for the Nature Conservation and Maintaining the Cultural Pluralism. This research also found that festivals are an important medium for cultural learning between generations and contribute to building social integration. Through meetings between spectators and participants, the Takbiran festival can erode conflict and social divisions, especially those resulting from the spread of hatred on social media.